Effect of chitosan coating on chilling injury, antioxidant status and postharvest quality of Japanese cucumber during cold storage - Nur Fatin Afifah Hashim; Azhane Ahmad; Paa Kwesi Bordoh (Penerbit Universiti Kebangsaan Malaysia, 2018)
Japanese cucumber (Cucumis sativus L.) could easily develop chilling injury when held at 7°C or below, thus limiting its storability and reduces consumer preference. Chitosan coating is known to be one of the methods used for preserving perishable fresh produce. This work was extended out to look into the efficacy of low molecular weight (LMW) chitosan coatings on chilling injury (CI), antioxidant levels and shelf life quality of Japanese cucumber. Fruit were coated with 0.5, 1.0 and 1.5% chitosan prior to cold storage at 7°C and 90-95% relative humidity (RH) for 12 days. The result showed that fruit coated with lowest concentration of chitosan (0.5%) was the most effective in alleviating chilling injury symptoms and reduced the increase of lipid peroxidation (MDA content) compared to higher concentrations (1.0 and 1.5%). Furthermore, when Japanese cucumbers were coated with 0.5% chitosan, it was able to maintain the postharvest quality and storability with higher firmness and delayed increase of weight loss. On the other hand, cucumber coated with 1.5% chitosan demonstrated high level of ascorbate peroxidase (APX) and catalase (CAT) activities than in 0.5 and 1.0% chitosan. This finding suggests a role for chitosan coating in alleviating oxidative stress that would lead to CI problems during cold storage.